Henry Dresser and Victorian Ornithology : birds, book and business - McGhie, Henry A. (Manchester University Press, 2017)
This book explores the life of Henry Dresser (1838-1915), one of the most productive British ornithologists of the mid-late nineteenth and early twentieth centuries. Dresser travelled widely and spent time in Texas during the American Civil War. The book explores how he and his contemporaries discovered the world's birds in farflung places. It also explores changes (and arguments) in scientific society over time.